Evaluation of street sweeping and washing to reduce ambient PM10. (4th January 2008) - Chou, Chih-Mei; Chang, Yu-Min; Lin, Wen-Yinn; Tseng, Chao-Heng; , Luke Chen
This paper presents an evaluation of street sweeping and washing by PM10 measurements and determination of silt load from active traffic streets. A modified Regenerative-Air Vacuum Sweeper (RAVS) and a washer were used. It was found that the impact of sweeping alone on ambient PM10 concentrations was short-lived, lasting no more than about 2?3 h. The method of sweeping followed by washing tested in this work was found to offer a measurable reduction in PM10 re-suspension potentials from paved roads. Typically, the reduction efficiency is up to 24.4% of ambient PM10 concentration. Finally, correlated with ηs (based on silt load), a correlation is proposed to estimate the reduction efficiency, ηr (based on PM10), which is valid in appropriate conditions suggested by the work. It is feasible to predict the reduction efficiency of ambient PM10 controlled by the RAVS and washer used in this work.